PENGARUH KEBIJAKAN DIVIDEN, STRUKTUR HUTANG, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA - Herman Paleni; Fiter Xarnes Pradana (LPPM UNIVERSITAS BINA INSAN, 2025)
This study aims to assess the effect of dividend policy, debt policy, and profitability of oil and gas sub-sector companies listed on the Indonesia Stock Exchange for the years 2019-2022. The method applied in this study is quantitative and uses panel data regression with a sample of 14 companies. The model testing uses the Chow Test, Hausman Test, and Lagrange Multiplier, and the results show that the Random Effect Model is the most appropriate. The results show that the Dividend Payout Ratio (DPR) has a significant positive effect on Price to Book Value (PBV), indicating that dividend policy is a driver for companies. On the other hand, the Debt Equity Ratio (DER) and Return on Equity (ROE) do not have a significant effect on PBV. However, when taken together, DPR, DER, and ROE have an effect on PBV with a coefficient of determination (R2) of 13.47%. This indicates that, in the oil and gas sub-sector, investors pay more attention to the consistency of dividend policy than debt policy and profitability in evaluating company performance. The practical and managerial implications that can be drawn from this study are the need for company management to maintain and sustain dividend policy in the long term in order to increase investor confidence and enhance company value.